2017
DOI: 10.1111/hcre.12108
|View full text |Cite
|
Sign up to set email alerts
|

Pornography Consumption and Satisfaction: A Meta-Analysis

Abstract: A classic question in the communication literature is whether pornography consumption affects consumers' satisfaction. The present paper represents the first attempt to address this question via meta‐analysis. Fifty studies collectively including more than 50,000 participants from 10 countries were located across the interpersonal domains of sexual and relational satisfaction and the intrapersonal domains of body and self satisfaction. Pornography consumption was not related to the intrapersonal satisfaction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
115
6
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(130 citation statements)
references
References 86 publications
7
115
6
2
Order By: Relevance
“…Furthermore, exposure to pornography accounts for more of the variability in an adolescent's decision to have sex than parents, religion, or school (Kingston, Malamuth, Fedoroff, & Marshall, 2009). Among male adults, Internet pornography use is positively associated with having multiple sex partners, engaging in paid sex, and engaging in extramarital sex (Wright & Randall, 2012;Wright, Tokunaga, Kraus, & Klann, 2017). However, less is known about the association between Internet pornography and sexual behavior among adult women.…”
Section: Pornography Use and Sexual Behaviormentioning
confidence: 99%
“…Furthermore, exposure to pornography accounts for more of the variability in an adolescent's decision to have sex than parents, religion, or school (Kingston, Malamuth, Fedoroff, & Marshall, 2009). Among male adults, Internet pornography use is positively associated with having multiple sex partners, engaging in paid sex, and engaging in extramarital sex (Wright & Randall, 2012;Wright, Tokunaga, Kraus, & Klann, 2017). However, less is known about the association between Internet pornography and sexual behavior among adult women.…”
Section: Pornography Use and Sexual Behaviormentioning
confidence: 99%
“…Although numerous studies (reviewed below) have indicated that frequent pornography use is associated with sexual and relationship dissatisfaction, relatively few studies have investigated possible drivers of these associations. Some authors (Wright, Tokunaga, Kraus, & Klann, ) have suggested that pornography use negatively impacts sexual and relationship satisfaction by distorting consumers' conceptions of what sexual practices are normative and satisfying. It is argued that exposure to the messages contained within pornography creates a preference for the kinds of sexual practices commonly depicted in pornography (i.e., a preference for “porn‐like” sex), which leads porn users to feel sexually dissatisfied when their preferences are not met by their sexual partners.…”
Section: Introductionmentioning
confidence: 99%
“…Even among the significant results, estimates of the magnitude of these effects tend to vary. Fortunately, Wright, Tokunaga, et al () recently conducted a meta‐analysis of studies assessing pornography's impact on intrapersonal (body image and sexual self‐esteem) and interpersonal satisfaction (relationship and sexual satisfaction). This meta‐analysis found an average correlation between pornography use and interpersonal satisfaction of −0.10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, scholars have begun to investigate what role pornography use plays in romantic relationship satisfaction, with much of the findings indicating that pornography has a negative impact on relationships (Wright, Tokunaga, Kraus, & Klann, 2017). Pornography use is often studied through the lens of Social Cognitive (Bandura, 2001) and Sexual Scripting (Simon & Gagnon, 2003) theories.…”
mentioning
confidence: 99%